Parametric sets for frames in Walsh analysis - Farkov, Ю.А. (Bulletin of L.N. Gumilyov Eurasian National University. Mathematics, computer science, mechanics series, 2018)
Parametric frame sets in the Walsh analysis are introduced and the corresponding algorithms for constructing the Parseval frames are indicated. Relationships with constructions of orthogonal wavelets on Vilenkin groups and in spaces of periodic sequences of complex numbers are noted.